Chiral Optical Properties of Phenyloxazoline Derivatives that Appear Only in the Solid State. Issue 4 (20th December 2013) - Hirayama, Masato; Kobayashi, Yuhei; Tanaka, Yuki; Sato, Tomohiro; Harada, Takunori; Tajima, Nobuo; Kuroda, Reiko; Fujiki, Michiya; Imai, Yoshitane
Abstract: Unlike in the solution state, the circularly polarized luminescence (CPL) of the chiral oxazoline compound 4‐(4‐isopropyl‐4, 5‐dihydrooxazol‐2‐yl)benzonitrile, having one oxazoline unit, was observed in the solid state. On the other hand, although the CPL of the chiral oxazoline compound 1, 4‐bis(4‐isopropyl‐4, 5‐dihydrooxazol‐2‐yl)benzene, having two oxazoline units, was not observed, its circular dichroism (CD) property changed significantly according to the state (i.e., solution or solid state). Abstract : Unlike in the solution state, circularly polarized luminescence (CPL) of the chiral oxazoline compound 4‐(4‐isopropyl‐4, 5‐dihydrooxazol‐2‐yl)benzonitrile was observed in the solid state. The CPL of chiral 1, 4‐bis(4‐isopropyl‐4, 5‐dihydrooxazol‐2‐yl)benzene, having two oxazoline units, was not observed, but its circular dichroism (CD) property changed significantly according to the physical state.